"A Most Detestable Crime": Gender Identities and Sexual Violence in the District of Montreal, 1803-1843 - Ramos, Sandy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
Keywords: Femmes

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Pratiques et stratégies spatiales des employées de bureau montréalaises dans un contexte de décentralisation économique - Chicoine, Nathalie (Institut national de la recherche scientifique et Université du Québec à Montréal, 2001)
Keywords: Femmes; Travail

The Feminization of Clerical Work in Early Twentieth-Century Montreal - Boyer, Laura Kate (Université McGill, 2001)
Keywords: Femmes; Travail

Vive la Canadienne! Les représentations de l’identité féminine dans le défilé de la Saint-Jean-Baptiste à Montréal (1924-1961) - Demers, Michel (Université de Sherbrooke, 2001)
Keywords: Femmes; Saint-Jean-Baptiste (fête)